Ke Arah Pendidikan di Wilayah Perbatasan : Studi Kasus Perbatasan Kalimantan Timur (Indonesia) - Malaysia - Anis Masykhur (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2010)
this article discusses the educational condition in the borders of northern part of East Kalimantan, one og the strategic areas being the veranda of Indonesia. to improve the educational quality there, it is necessary to specifically take into account the condition of those living in such geography. in addition, their lifestyle must also be accommodated in an educational orientation to benefit them because they are mostly farmers and fishermen. to strengthen the religious content, a “boarding" model like pesantren must be considered. for affordable educational expenses, more effective cooperation patterns between the government and the community must be attained, formulated, and implemented.